Behavioral Clinical Trials in Moderate to Severe Pediatric Traumatic Brain Injury: Challenges, Potential Solutions, and Lessons Learned. Issue 6 (November 2017) - Wade, Shari L.; Kurowski, Brad G.
Abstract : N/A: The purpose of this commentary is to outline the challenges encountered when conducting clinical trials of interventions for pediatric traumatic brain injury (TBI) and share potential solutions for surmounting these issues. This commentary grows out of our experience implementing 8 randomized clinical trials (RCTs) of family-centered interventions to reduce child behavior problems and caregiver/parent distress following pediatric brain injury. These studies, involving more than 600 participants from 8 clinical centers, support the feasibility of conducting RCTs with children who have sustained TBIs while highlighting potential challenges and threats to validity. The challenges of behavioral trials for pediatric TBI are apparent but not insurmountable. Careful consideration of the clinical trial issues outlined in this commentary can inform design choices and analyses when planning a clinical trial. It is critically important that investigators share their failures as well their successes to move the field of pediatric TBI intervention research forward.